Acne vulgaris: Perceptions and beliefs of Saudi adolescent males - Sahar H Al-Natour (Wolters Kluwer Medknow Publications, 2017)
Introduction: Although acne vulgaris is common in adolescents, information on their understanding of acne is minimal. Objectives: To evaluate the perceptions and beliefs of Saudi youth on acne. Materials And Methods: Three hundred twenty-nine male students (aged 13-22 years) from 6 secondary schools in the Eastern Saudi Arabia completed a self-reported questionnaire on knowledge, causation, exacerbating and relieving factors of acne. Data were analyzed by SPSS version 15.0. Results of subjects with acne, a family history of acne, and parents' educational levels were compared. Differences between the analyzed groups were assessed by a Chi-square test; p ≤ 0.05 was considered statistically significant. Results: Over half (58.9%) of the participants considered acne a transient condition not requiring therapy. Only 13.1% knew that the proper treatment of acne could take a long time, even several years. Over half (52%) thought acne can be treated from the first or after few visits to the doctor. Popular sources of information were television/radio (47.7%), friends (45.6%), and the internet (38%). Only 23.4% indicated school as a source of knowledge. Reported causal factors included scratching (88.5%) and squeezing (82.1%) of pimples, poor hygiene (83.9%), poor dietary habits (71.5%), and stress (54.1%). Ameliorating factors included frequent washing of the face (52.9%), exercise (41.1%), sunbathing (24.1%), and drinking of mineral water (21%). The correlations of these facts are discussed. Conclusion: Results of this study point out that misconceptions of acne are widespread among Saudi youth. A health education program is needed to improve the understanding of the condition.